Analysis Spatial Pattern Garbage Bank using Web Geographic Information System in Yogyakarta City - Vidyana Arsanti; Rizqi Sukma Kharisma; Sidiq Arfianto (Advance Sustainable Science Engineering and Technology, 2023)
Minimizing waste with independent waste management realizes the 3-R principle, one of which is the waste bank program. There are 448 waste banks in the entire city of Yogyakarta, which is about 73% of the total RW in the city of Yogyakarta. However, from this data, the visual form of the spatial distribution of waste banks in Yogyakarta City has yet to be discovered with certainty. This quantitative research analyzes the distribution pattern of waste banks in Yogyakarta City using the Nearest Neighbor Analysis method. The objectives of this study are (1) to determine the visual form of the spatial distribution of waste banks in the city of Yogyakarta; (2) to analyze the distribution pattern of waste banks in the city of Yogyakarta. The results are (1) The visual form of the spatial distribution of waste banks in Yogyakarta City is spread in almost all areas of Yogyakarta City, with an area of 32.5 km2. Waste Banks that have been plotted locations are 448 waste banks; (2) The distribution pattern of the waste bank in the city of Yogyakarta is dispersed or uniform/regular distribution pattern.